Identification of long non-coding RNA and circular RNA associated networks in cellular stress responses - Li, Xiuzhi; Li, Jingxin; Shan, Ge; Wang, Xiaolin (Frontiers in Genetics, 2023)
Mammalian cells employ various adaptive responses to cope with multiple stresses to maintain homeostasis. Functional roles of noncoding RNAs (ncRNAs) in response to cellular stresses have been proposed, and systematical investigations about the crosstalk among distinct types of RNAs are required. Here, we challenged HeLa cells with thapsigargin (TG) and glucose deprivation (GD) treatments to induce endoplasmic reticulum (ER) and metabolic stresses, respectively. Ribosomal RNA (rRNA)-depleted RNA sequencing (RNA-seq) was then performed. Characterization of the RNA-seq data revealed a series of differentially expressed long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) with parallel changes responsive to both stimuli. We further constructed the lncRNA/circRNA-mRNA co-expressing network, competing endogenous RNA (ceRNA) network in the lncRNA/circRNA-miRNA-mRNA axis, and lncRNA/circRNA-RNA binding protein (RBP) interactome map. These networks indicated the potential cis and/or trans regulatory roles of lncRNAs and circRNAs. Moreover, Gene Ontology (GO) analysis demonstrated that these identified ncRNAs were associated with several essential biological processes known to be related to cellular stress responses. In conclusion, we systematically established functional regulatory networks of lncRNA/circRNA-mRNA, lncRNA/circRNA-miRNA-mRNA and lncRNA/circRNA-RBP to perceive the potential interactions and biological processes during cellular stresses. These results provided insights in ncRNA regulatory networks of stress responses and the basis for further identifying of pivotal factors involved in cellular stress responses.